1998
DOI: 10.1091/mbc.9.7.1757
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Temperature-sensitive Lethal Alleles in Essential β-Tubulin and Nonessential α2-Tubulin Genes as Fission Yeast Polarity Mutants

Abstract: We have screened for temperature-sensitive (ts) fission yeast mutants with altered polarity (alp1-15). Genetic analysis indicates that alp2 is allelic to atb2 (one of two ␣-tubulin genes) and alp12 to nda3 (the single ␤-tubulin gene). atb2 ϩ is nonessential, and the ts atb2 mutations we have isolated are dominant as expected. We sequenced two alleles of ts atb2 and one allele of ts nda3. In the ts atb2 mutants, the mutated residues (G246D and C356Y) are found at the longitudinal interface between ␣/␤-heterodim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 80 publications
6
79
2
1
Order By: Relevance
“…The effect of EF1␣ overproduction on the microtubule cytoskeleton seems to be inconsistent with the previous observation that EF1␣ possesses microtubule-severing activity (Shiina et al 1994). Curled microtubules were frequently observed in the fission yeast alp (Radcliffe et al 1998;Hirata & Toda, unpublished observations) or tea1 mutant cells (Mata & Nurse 1997). Some alp genes encode microtubule-associated proteins that are important for the expression of the function of the microtubule (Hirata et al 1998a;Radcliffe et al 1998).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The effect of EF1␣ overproduction on the microtubule cytoskeleton seems to be inconsistent with the previous observation that EF1␣ possesses microtubule-severing activity (Shiina et al 1994). Curled microtubules were frequently observed in the fission yeast alp (Radcliffe et al 1998;Hirata & Toda, unpublished observations) or tea1 mutant cells (Mata & Nurse 1997). Some alp genes encode microtubule-associated proteins that are important for the expression of the function of the microtubule (Hirata et al 1998a;Radcliffe et al 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Curled microtubules were frequently observed in the fission yeast alp (Radcliffe et al 1998;Hirata & Toda, unpublished observations) or tea1 mutant cells (Mata & Nurse 1997). Some alp genes encode microtubule-associated proteins that are important for the expression of the function of the microtubule (Hirata et al 1998a;Radcliffe et al 1998). Tea1 also functions in the microtubule cytoskeleton and is important for generating global spatial order (Mata & Nurse 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Since the nucleus is kept in the cell middle by the opposing pushing forces exerted by microtubule plus ends on the cell tips [Tran et al, 2001], the division site is therefore placed in the cell middle. In fact, this hypothesis was first formulated from the analysis of microtubule defective mutants displaying delocalized nuclei and septa [Toda et al, 1983;Radcliffe et al, 1998]. More recent studies, in the same spirit as the spindle displacement experiments developed by Ray Rappaport in marine eggs [Rappaport, 1985], have shown that displacing the nucleus from the cell middle by cell centrifugation in the absence of microtubules, or using optical tweezers, indeed results in the delocalization of contractile rings and septa to the new position occupied by the nucleus [Daga and Chang, 2005;Tolic-Norrelykke et al, 2005; see Fig.…”
Section: The Nucleus Influences Mid1 Cortical Localizationmentioning
confidence: 99%
“…A parental strain (KZ2 ; Table 1), which contains minichromosome Ch16 (Niwa et al, 1989) and Bub1-GFP was mutagenized with nitrosoguanidine as described previously (Radcliffe et al, 1998), spread on rich YE5S plates and incubated at 27°C. Colonies were replica-plated onto YE5S at 36°C and YE plates (rich medium lacking exogenously added supplements) at 32°C, on which cells that had lost Ch16 turned red because of the chromosomal ade6-210 mutation (Niwa et al, 1989).…”
Section: Isolation Of Cin Mutantsmentioning
confidence: 99%
“…On the other hand, in the ts ␤-tubulin mutant (nda3-1828), which loses the MT structure at the restrictive temperature (Radcliffe et al, 1998), and is therefore expected to contain unattached kinetochores, 60% of cells showed Bub1 at the kinetochore at 36°C and even at the permissive temperature (26°C), Bub1 localized to the kinetochore in a higher proportion of cells (6.2%; Figure 1B). In the case of the rad21-K1 mutant defective in cohesion, which is also required for bipolar attachment of the kinetochore to the spindle (Tatebayashi et al, 1998;Tanaka et al, 2000), a higher value of Bub1 dots (3.0% at 26°C and 5.6% at 36°C) was obtained.…”
Section: Isolation Of Fission Yeast Mutants With Defects In Spindle-kmentioning
confidence: 99%